2007
DOI: 10.1038/sj.jp.7211770
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic/racial diversity, maternal stress, lactation and very low birthweight infants

Abstract: Objective: (1) To compare maternal characteristics and psychological stress profile among African-American, Caucasian and Hispanic mothers who delivered very low birthweight infants. (2) To investigate associations between psychosocial factors, frequency of milk expression, skin-to-skin holding (STS), and lactation performance, defined as maternal drive to express milk and milk volume.Study Design: Self-reported psychological questionnaires were given every 2 weeks after delivery over 10 weeks. Milk expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 71 publications
5
56
1
3
Order By: Relevance
“…27,28 A majority of factors negatively influencing milk volume in lactating mothers are not amendable to change, so clinicians must focus on modifiable interventions to increase milk volume. 13 Although some study findings have confirmed that earlier initiation of milk expression following delivery improves milk supply in mothers of VLBW infants, 26,28,38 many mothers delay milk expression for hours to days following delivery, which may negatively impact milk volume. Mothers should be encouraged and provided with support to initiate milk expression as soon as possible after delivery, preferably within the first hour.…”
Section: Discussionmentioning
confidence: 93%
“…27,28 A majority of factors negatively influencing milk volume in lactating mothers are not amendable to change, so clinicians must focus on modifiable interventions to increase milk volume. 13 Although some study findings have confirmed that earlier initiation of milk expression following delivery improves milk supply in mothers of VLBW infants, 26,28,38 many mothers delay milk expression for hours to days following delivery, which may negatively impact milk volume. Mothers should be encouraged and provided with support to initiate milk expression as soon as possible after delivery, preferably within the first hour.…”
Section: Discussionmentioning
confidence: 93%
“…Because attainment of independent oral feeding is one of the criteria recommended by the American Academy of Pediatrics for hospital discharge (1), the longer these infants' transition from tube to independent oral feeding, the longer their hospitalization (2,3). Consequently, prolonged oral feeding difficulties increase medical costs and potential long-term oral feeding aversion and further increase maternal stress as mother-infant reunion is delayed (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Adicionalmente, no se obtuvo información acerca de otros factores que se han relacionado con el estrés parental, como lactancia materna, ansiedad y depresión. 18,32 La mayor fortaleza de este estudio es que incluye un importante número de centros y provee información novedosa para la región sudamericana.…”
Section: Discussionunclassified